2018
DOI: 10.4314/sajas.v48i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic <i>Bacillus</i> species and <i>Saccharomyces boulardii</i> improve performance, gut histology and immunity in broiler chickens

Abstract: The aim of this study was to compare the effects of a new multispecies probiotic containing four Bacillus species and Saccharomyces boulardii (Microguard ® ) with a commercial probiotic (Protexin ® ) and a commonly used antibiotic in broilers. Six hundred one-day-old male Ross 308 broilers were randomized to six experimental treatments, with five replicates of 20 chicks each, for 42 days, receiving an ad libitum cornsoybean basal diet. Treatments were added to the basal diet and consisted of tetracycline as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
(62 reference statements)
5
23
1
Order By: Relevance
“…However, probiotic addition seemed to be beneficial, particularly when added to a 30% blue lupine diet, which exhibited higher crude fiber and low amino acid concentrations, causing an improvement of 2.71, 1.34, and 4.07% in growth rate, FCR, and EPEI, respectively. These results are similar to those reported by (24,25,35,54,55), who found that probiotics containing Bacillus spp. and Saccharomyces boulardii benefit the production performance of broilers from 1 to 28 d of age.…”
Section: Growth Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…However, probiotic addition seemed to be beneficial, particularly when added to a 30% blue lupine diet, which exhibited higher crude fiber and low amino acid concentrations, causing an improvement of 2.71, 1.34, and 4.07% in growth rate, FCR, and EPEI, respectively. These results are similar to those reported by (24,25,35,54,55), who found that probiotics containing Bacillus spp. and Saccharomyces boulardii benefit the production performance of broilers from 1 to 28 d of age.…”
Section: Growth Performancesupporting
confidence: 92%
“…In general, probiotic addition had a beneficial effect on the bursa, thymus, and spleen percentages of broilers that were not fed blue lupine at 35 d of age. These results are similar to those reported by (55,57), who found that the addition of probiotics improved the immune index of broiler chickens and beneficially modulated gut microflora, particularly in the ceca area and resulted in enhanced growth (23)(24)(25).…”
Section: Immune Organs At 21 and 35 D Of Agesupporting
confidence: 91%
See 1 more Smart Citation
“…Such an alternative would be the use of probiotics, which are live microbial products that are beneficial to the host through an improved microbial equilibrium in the intestines (Abdulla et al, 2015). The most commonly used probiotic bacteria in poultry are Lactobacillus, Bifidobacterium, Bacillus, Streptococcus, Pediococcus and Enterococcus species (Manafi et al, 2018). The efficacy of probiotics in altering gut microbial balance, leading to enhanced feed utilization, growth performance and increased immunity, is well documented (Chichlowski et al, 2007;Taherpour et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Various Bacillus species, including Bacillus subtilis have been used as additives for their positive effects of improving the antioxidant capacity in poultry production. Manafi et al (2018) proved that spores of Bacillus subtilis are good candidates as a feed additive because this additive led to a reduction in protein and amino acid requirements for broiler chickens and, consequently, that the feed cost per kilogram weight gain could be reduced. However, the benefits of its use are not always observed unless they are associated with antibiotics.…”
Section: Introductionmentioning
confidence: 99%